2018
DOI: 10.1002/lary.27557
|View full text |Cite
|
Sign up to set email alerts
|

Are chronic cough and laryngopharyngeal reflux more common in obstructive sleep apnea patients?

Abstract: Objectives/Hypothesis To assess if there is a significant difference in the prevalence and severity of chronic cough symptoms in obstructive sleep apnea (OSA) patients versus non‐OSA patients and examine this relationship in regard to laryngopharyngeal reflux (LPR) symptoms. Study Design Prospective cohort study. Methods Patients referred to Northwestern Medicine Sleep Lab for home sleep testing were enrolled. Patients filled out the Leicester Cough Questionnaire (LCQ) and Reflux Symptom Index (RSI) before com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 38 publications
(55 reference statements)
2
20
0
Order By: Relevance
“…[28][29][30] Our prior report, with a smaller sample size (n = 52), found that the symptoms of chronic cough and LPR as measured by the LCQ and RSI, respectively, were worse among those with OSA. 34 In this study, we demonstrate this prior finding holds with a larger sample size. We further find that of the otolaryngologic symptom questionnaires we assessed, only these two symptom questionnaires have potential discriminatory ability for identifying OSA patients.…”
Section: Discussionsupporting
confidence: 60%
“…[28][29][30] Our prior report, with a smaller sample size (n = 52), found that the symptoms of chronic cough and LPR as measured by the LCQ and RSI, respectively, were worse among those with OSA. 34 In this study, we demonstrate this prior finding holds with a larger sample size. We further find that of the otolaryngologic symptom questionnaires we assessed, only these two symptom questionnaires have potential discriminatory ability for identifying OSA patients.…”
Section: Discussionsupporting
confidence: 60%
“…Several clinical studies have demonstrated that patients with OSA are associated with various types of LAH such as chronic cough (Sundar and Daly, 2011;Chan et al, 2015;Gouveia et al, 2019). Sensitization of laryngeal afferents has been implicated in the pathogenesis of chronic cough (Novakovic and MacKay, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Among these laryngeal afferents, capsaicin-sensitive superior laryngeal nerves (SLNs), constituting a subpopulation of nociceptive-like free nerve endings, are highly sensitive to various inflammatory mediators (Tsai et al, 2009;Liu et al, 2013). Activation of capsaicin-sensitive SLNs may evoke a number of respiratory reflexes, such as apnea, cough, and glottis-stop reflex (Prudon et al, 2005;Liu et al, 2013), many of which are clinical signs of patients with OSA (Novakovic and MacKay, 2015;Gouveia et al, 2019). Also, patients with OSA exhibit chronic cough, a major symptom of LAH, which may be related to the degree of inflammatory markers in the airways (Chan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of OSA was made using attended polysomnography at the University of Utah Sleep-Wake Center-an American Academy of Sleep Medicine accredited sleep laboratory. Each participant had an AHI score which was used to classify OSA as mild (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), moderate (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), or severe (≥30) [40]. Confirmed OSA patients who were 18 years or older, able to communicate in English, and had no known cognitive deficits were invited to participate in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…With more severe OSA, the extent of sexual dysfunction, incontinence, and poorer QOL increases (especially among women) [3,4]. However, recent research has also established that OSA often presents with evidence of potential upper airway related problems involving longstanding voice problems, chronic refractory cough, and diurnal dyspnea, particularly among women [5][6][7][8][9][10][11]. Although the origin of such problems in OSA is likely multifactorial [8,11,[12][13][14][15][16][17][18][19][20][21][22][23], it has been postulated that this constellation of voice, cough, and diurnal dyspnea might reflect upper airway inflammation (a common feature of OSA) and/or possible laryngeal hypersensitivity and related laryngeal motor dysfunction [5,11,22,23].…”
Section: Introductionmentioning
confidence: 99%